Regulation of Thromboplastin Synthesis in Mouse Placental Cells In Vitro - Dalaker, Knut; Prydz, Hans (Thrombosis and Haemostasis, 1983)
Mouse placental cells are probably constitutive producers of the thromboplastin apoprotein in vitro. The effect of cyclic AMP- elevating compounds on their expression of thromboplastin activity has been studied. Dibutyryl cyclic AMP, the phosphodiesterase inhibitor Ro 20-1724 and the adenyl cyclase stimulator forskolin all decrease the synthesis of thromboplastin. Prostaglandin E2 and the phosphodiesterase inhibitor butyl-methyl-xanthine have a biphasic dose dependent effect. A stimulation was observed at low concentrations, whereas higher doses decreased the synthesis of thromboplastin. Adrenaline had no effect. Combination of two compounds, each at maximally inhibiting concentration gave no significant additive inhibitory effect, showing that they probably act via the same pathway.
Keywords: Thromboplastin; Tissue factor; Placenta; Cyclic AMP; Adenyl cyclase stimulators; Phosphodiesterase inhibitors